PERANCANGAN HARVEST CONVENTION CENTER DENGAN PENDEKATAN ARSITEKTUR FUTURISTIC DI HARVEST CITY KECAMATAN CILEUNGSI KABUPATEN BOGOR JAWA BARAT - Jungjung Munte; Purnama Sakhrial Pradini; Isria Maherni Maherti Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
Convention Center is a center/container for meeting activities attended by a group for common interests. Harvest city is located in Cileungsi District, which is located in Bogor Regency, West Java Province. Cileungsi District is a very dense district with very rapid economic growth and is a business center area with very diverse and many activities. Harvest City itself is a very strategic location with a fairly dense population close to big cities such as Jakarta, Bekasi, Bogor, Cikarang, Depok, Cibubur, and many other cities. Harvest City is easily accessible with several alternative transportation supports such as terminals, toll roads, and is a very strategic location because it is close to shopping centers, hospitals, schools and others. With the high population and high economic activity in the Cileungsi sub-district, of course it requires a container or place that can accommodate various existing activities. Activities such as product exhibitions, shows, product launches, seminars, business and non-business meetings certainly need a place. Every citizen of Cileungsi who will hold meetings, whether weddings, seminars, product launches, music concerts and others. From there came the idea to create a multipurpose building that aims to facilitate these activities, it is necessary to make a public facility multipurpose building to meet the needs of public facilities in this city. Because of the need for space for this general facility, the author makes a design to fulfill every analysis in this area. By applying an unusual concept, it will add motivation to everyone who plays a role in using the facilities of this meeting building so as to produce an architectural work that has the maximum function and aesthetics possible